Feasibility Study for the Construction of the Dekranasda Gallery Building in Pangkalpinang City - Putri Ayu Dwiyana; Junita Eka Susanti (Universitas Islam Raden Rahmat, Malang, 2025)
The construction of the Dekranasda Gallery Building in Pangkalpinang City is planned as part of a strategy to strengthen the creative economy sector and increase the added value of local craft products. This study aims to identify the priority location for the construction of the Dekranasda Gallery Building by evaluating three alternative sites from technical, economic, social, and environmental perspectives. Each aspect is analyzed by considering the availability of basic infrastructure, land use suitability, investment value, and community perception and social support for the gallery's construction. The assessment is carried out comparatively to obtain the most optimal location recommendations. The analysis results show that Alternative Location 1 (Taman Mandara) has the highest overall score, relatively complete infrastructure support, good social suitability, and an estimated investment requirement of IDR 13,929,500,000. Alternative Location 2 (Tampuk Pinangpura) shows a reasonably good feasibility value but is not yet optimal from a technical perspective. Meanwhile, Alternative Location 3 (Tugu Kepiting) has limited infrastructure and a low social score, requiring a higher investment of IDR 14,229,500,000. Considering all aspects of feasibility, Alternative Location 1 is recommended as a priority location for constructing the Pangkalpinang City Dekranasda Gallery Building.